River Classification as a Geographic Tool in the Age of Big Data and Global Change. - Praskievicz, Sarah (Geographical Review, 2018)
Spatial classification is a well-defined analysis method in geography, which involves defining regions of the Earth based on shared characteristics. An analogy can be made between classification in geography and taxonomy in biology, because both are used to reduce complexity. Just as modern evolutionary theory and genetics technologies have transformed biological taxonomy from the sometimes arbitrary classification of living things based on superficial similarities and differences into a system that reflects the history of life and relationships among organisms, modern advances in conceptual understanding and development of technology have similarly revolutionized classification in geography as a powerful method for describing and quantifying processes. Here, I describe the history and current trends of geographic classifications relevant to river systems. Overall, there is significant emerging potential in classification as a tool for understanding river processes